DIGITALISASI UMKM MELALUI E-COMMERCE SEBAGAI PENINGKATAN PENDAPATAN NASIONAL - Yuli Setiawan (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2023)
Currently, the era of the digital economy has become a momentum for businessmen to compete in creating innovative and sustainable business strategies. Advances in digital technology have also had a significant impact on various aspects of the global economy, one of the units that contribute to national income is Micro, Small, and Medium Enterprises (MSMEs). nowadays, the number of MSMEs that have gone digital is still around 12% of the total MSMEs in Indonesia. This research method uses qualitative methods, through investigation, description, and explanation of the quality or importance of digitizing MSMEs through e-commerce on national income which cannot be explained, measured, and described through a quantitative approach. The results of this study indicate that the digitization of MSMEs has a significant influence on increasing national income.